Choosing Wisely Portugal – Escolhas Criteriosas em Saúde - Miguel Bigotte Vieira; Guilherme Ferreira dos Santos; Catarina Reis de Carvalho; Catarina Viegas Dias; David Cordeiro Sousa; Inês Leal; João Valente Jorge; Mariana Alves; Mariana Morgado; Rute Baeta Baptista; Paula Fortunato; António Vaz Carneiro; et al. (Acta Médica Portuguesa, 2018)
n/d